Incubation of canine dermal fibroblasts with serum from dogs with atopic dermatitis activates extracellular matrix signalling and represses oxidative phosphorylation - Colitti M.; Stefanon B.; Sandri M.; Licastro D. (Veterinary Research Communications, 2022)
The aim of this study was to investigate the effects on gene expression in canine fibroblasts after incubation with a medium enriched with atopic dermatitis canine serum (CAD) compared with healthy canine serum (CTRL) and fetal bovine serum (FBS). Differential Expression and Pathway analysis (iDEP94) in R package (v0.92) was used to identify differentially expressed genes (DEGs) with a False Discovery Rate of 0.01. DEGs from fibroblasts incubated with CAD serum were significantly upregulated and enriched in the extracellular matrix (ECM) and focal adhesion signalling but downregulated in the oxidative phosphorylation pathway. Genes involved in profibrotic processes, such as TGFB1, INHBA, ERK1/2, and the downward regulated genes (collagens and integrins), were significantly upregulated after fibroblasts were exposed to CAD serum. The observed downregulation of genes involved in oxidative phosphorylation suggests metabolic dysregulation toward a myofibroblast phenotype responsible for fibrosis. No differences were found when comparing CTRL with FBS. The DEGs identified in fibroblasts incubated with CAD serum suggest activation of signalling pathways involved in gradual differentiation through a myofibroblast precursors that represent the onset of fibrosis. Molecular and metabolic knowledge of fibroblast changes can be used to identify biomarkers of the disease and new potential pharmacological targets.